Energy and macronutrient intakes of professional football (soccer) players. Issue 1 (March 1997) - Maughan, R J
Abstract : OBJECTIVE: To examine the dietary habits of professional soccer players at two Scottish Premier League clubs during the competitive season. METHODS: A study of the dietary intake of 51 professional soccer players with two different clubs was carried out by the seven day weighed intake method. RESULTS: Physical characteristics of the two groups of players were similar, with only small differences in age and body mass but no difference in height and body fat. Mean (SD) daily energy intake for club A was 11.0 (2.6) MJ, and for club B 12.8 (2.2) MJ. The higher energy intake at club B was largely accounted for by a higher (P < 0.005) fat intake (118 v 93 g d-1): there was no difference in the absolute amounts of protein, carbohydrate, or alcohol consumed. When expressed as a fraction of total energy intake, mean protein intake was higher (P < 0.05) and fat intake lower (P < 0.01) at club A. CONCLUSIONS: The mean energy intake of these players was not high compared with athletes in endurance sports. Fractional contribution of the macronutrients to total energy intake was broadly similar to that of the general population.